Hormonal treatment of carcinoma of the prostate - Obata, K (Hinyokika kiyo. Acta urologica Japonica, 1991)
Efficacy of orchiectomy and intravenous administration of diethylstilbestrol diphosphate (DESP) for the treatment of prostatic carcinoma was evaluated on 184 patients treated between 1975 to 1989. The patients were between 49 to 88 years old with a mean age of 73.4 +/- 8.3 years. Clinical stage was A in 9.8%, B in 12%, C in 26.6% and D in 51.6%. The histologically well, moderately and poorly differentiated adenocarcinoma were observed in 20.9, 29.4 and 49.7%, respectively. The 5-year survival rate of stage A, B, C and D calculated with the Kaplan-Meier method were 90, 49, 60 and 34%, respectively. The 5- and 10-year survival rate of the patients who had received orchiectomy was 53 and 24%, respectively, while that of the patients without orchiectomy was 38 and 14%, respectively. The 5 and 7-year survival rate of the patients treated with intravenous administration of DESP was 54 and 34%, respectively while that of the patients without DESP was 46 and 31%, respectively. These findings suggest that orchiectomy and intravenous administration of DESP in any form prolonged patient survival compared with only oral administration of estrogens or antiandrogens. Reactivation was seen in 24 (40%) of the 60 patients under sufficient observation. Clinical relapse occurred within an average of 32.3 +/- 26.4 months after primary hormonal manipulation. The average time to relapse in stage D was shorter than that in stage B and C. Reactivation was observed in the patients on interrupted treatment earlier than in the patients on continuous administration of drugs. Cardiovascular death followed by endocrine therapy was 7.4% in this study